Use of Synthetic Salmon GnRH and Domperidone (Ovaprim®) in Sharks: Preparation for ex situ Conservation - Kim, Sang Wha; Hong, Won Hee; Han, Se Jin; Kwon, Jun; Ko, Heejun; Lee, Sung Bin; Giri, Sib Sankar; Kim, Sang Guen; Kim, Byung Yeop; Jang, Goo; Lee, Byeong Chun; Kim, Dong Wan; et al. (Frontiers in Marine Science, 2020)
Shark populations are constantly decreasing owing to environmental destruction and overfishing; thus, sharks are now at a risk of extinction, with 27.9% of shark species classified as endangered on the International Union for Conservation of Nature’s Red List. Sharks are apex predators and a keystone species in balancing the marine food chain; their extinction will create an imbalance of the entire marine ecosystem. Assisted reproductive technology is the last resort for protecting animals facing severe extinction. Here, as a proactive effort toward building a hormone-induced artificial insemination protocol for endangered wild sharks, we identified the possibility of germ cell maturation by administration of Ovaprim®, a commercially produced synthetic salmon gonadotropin-releasing hormone, and calculated its optimum dosage and injection timing. The experiment was conducted on two shark species—Triakis scyllium and Carcharhinus longimanus. We found that intramuscular injections of 0.2 mL/kg of Ovaprim® for male T. scyllium and C. longimanus, 0.2 mL/kg + 0.5 mL/kg at a 24 h interval for female T. scyllium, and 0.2 mL/kg + 0.2 mL/kg or 0.2 mL/kg + 0.3 mL/kg at a 24 h interval for female C. longimanus were optimal dose protocols. These doses effectively induced the maturation and ovulation of oocytes and the release of semen. Our results confirm that Ovaprim® is a suitable tool for shark hormone-induced artificial insemination and indicate that this method may enable the conservation of the endangered shark species.